The Palgrave Handbook of Animals and Literature
XXII, 636 p. 21 illus., 8 illus. in color.
Keywords: This volume is the first comprehensive guide to current research on animals, animality, and human-animal relations in literature. To reflect the history of literary animal studies to date, its primary focus is literary prose and poetry in English, while also accommodating emergent discussions of the full range of media and contexts with which literary studies engages, especially film and critical theory. User-friendly language, references, even suggestions for further readings are included to help newcomers to the field understand how it has taken shape primarily through recent decades. To further aid teachers, sections are organized by conventions of periodization, and chapters address a range of canonical and popular texts. Bookended by sections devoted to the field’s conceptual foundations and new directions, the volume is designed to set an agenda for literary animal studies for decades to come.